A heuristic method against simulation for optimal allocation of inspection stations in manufacturing systems. (November 2018) - Maleki, Hamed; Aghazadeh Shabestari, Aydin
Continuous improvement in quality is the most important mantra for success in today's competitive market. Previous studies indicated that although quality is the most important factor in gaining competitive superiority, increasing the level of quality alone cannot meet customers' needs. One complementary approach to improving the level of quality to meet customers' expectations is to lower the production costs and price of finished products. The quality circle as a path to achieve greater customer satisfaction is formed to identify the cost of quality and thus reduce this cost, which is a significant cost portion of the entire life cycle of products. This paper presents a case study in an electromotor manufacturing company. First, we build a mathematical model to allocate inspection stations to manufacturing processes and propose a heuristic approach to optimize it. Next, we use Enterprise Dynamic software for simulation. Finally, we compare these methods.